Reasonable investment: the legal sanitation as a mechanism for increasing the value of urban properties - Rivera Domínguez, Angello (2023)
This paper develops the economic benefits of legal sanitation as an effective mechanism to increase the value of urban Real Estate properties. It addresses the scenarios worthy of urban real estate property sanitation, the legal mechanisms to be undertaken and, finally, the legal transactions to be implemented in order to achieve an economic benefit for the parties involved.